ENHANCING SERVICE EFFICIENCY IN UTILITY ORGANIZATIONS THROUGH QUALITY FUNCTION DEPLOYMENT - Maryam Shahid; Rafiq Mansoor; Muhammad Shahid; Syed Athar Masood (International Journal of Management Studies)
Quality Function Deployment (QFD) is a powerful approach for establishing a strong relationship between a product or service and customer needs. It focuses on capturing the voice of the customer to enhance their satisfaction. In today’s competitive landscape, organizations must meet customer needs to thrive. This research focuses on utility-imparting organizations and aims to enhance customer satisfaction and service efficiency through the development of a correlation matrix. The study proposes an inductive framework and evaluates it using typical QFD techniques. Specifically, the research utilizes the House of Quality (HOQ) to improve organizational efficiency and customer satisfaction. The HOQ identifies key quality indicators by analyzing the relationship between customer needs (WHATs), and technical solutions (HOWs), as well as between different HOWs. The results of the HOQ analysis highlight the most crucial factors for improving service efficiency: effective customer service, a competitive and focused organization, accurate billing meters and methods, precise meter readings and billing, and prioritization of emergency response. The findings provide valuable guidelines for improving the efficiency of utility energy services.